2011
DOI: 10.3174/ajnr.a2643
|View full text |Cite
|
Sign up to set email alerts
|

Fractionated Radiation-Induced Acute Encephalopathy in a Young Rat Model: Cognitive Dysfunction and Histologic Findings

Abstract: BACKGROUND AND PURPOSE: Radiation-induced cognitive dysfunction is a common and serious complication after radiation therapy of brain tumor, yet knowledge of its mechanism is poorly understood. The aim of this study was to establish a young rat model for acute radiation encephalopathy, at both cognitive and pathologic levels, induced by fractionated irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 27 publications
2
38
1
2
Order By: Relevance
“…Absence of a difference in GFAP mRNA levels in hippocampus on the 4th and 8th week is probably due to initially higher expression of GFAP in this structure as compared with the frontal cortex. However, Zhou et al (2011) showed an increased expression of GFAP in hippocampus after fractionated gamma irradiation using immunohistochemical analysis. The latter result may be due to the higher dose of fractionation and a different fractionation mode.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Absence of a difference in GFAP mRNA levels in hippocampus on the 4th and 8th week is probably due to initially higher expression of GFAP in this structure as compared with the frontal cortex. However, Zhou et al (2011) showed an increased expression of GFAP in hippocampus after fractionated gamma irradiation using immunohistochemical analysis. The latter result may be due to the higher dose of fractionation and a different fractionation mode.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanism such as reactive astrogliosis are also involved in memory alteration (Zhou et al, 2011;Akiyama et al, 2001). Reactive astrogliosisis is typically characterized by astrocyte proliferation and hypertrophy (MacFabe et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estas últimas presentan gran potencia a dosis mínimas, actuando como sustancias antiinflamatorias o en procesos de resolución de procesos inflamatorios. Esto es de gran interés para evitar todos aquellos fenó-menos inflamatorios posibles precursores del deterioro cognitivo que se puede ocasionar por el uso de la radioterapia o la quimioterapia 10,11 .…”
Section: Funciones De Los áCidos Grasos Poliinsaturadosunclassified
“…However, cognitive impairment is a well-documented consequence of WBRT (1)(2)(3)(4). In addition to acute encephalopathy (5,6), memory deficits have been noted in up to 50% of patients undergoing WBRT over a short period of several months. In addition, WBRT is reported to increase the rate of dementia three-fold in younger patients (< 65 years old, up to around 0.2% of irradiated persons) (7) and to lower the intelligence quotient (IQ) of children (8) over the longer term, i.e.…”
Section: Introductionmentioning
confidence: 99%